The Effect of Firm Profit versus Personal Economic Well Being on the Level of Ethical Responses Given by Managers - Hoffman, James J. (Journal of business ethics, 1998)
Members of organizations are continually making decisions that have important consequences for themselves and the firms for which they work. In some cases these decisions affect human well being and social welfare and thus have important ethical impacts for those affected by the decisions., This study examines if certain strategic situations (enhancement of firm profits versus personal economic well being) cause decision makers to act more or less ethically. A questionnaire consisting of two vignettes which depicted actual business situations was used to collect data from 171 managers of a large Southeastern financial and communication conglomerate. Results from multivariate repeated measures tests suggest that managers will vary their level of ethical response when faced with a situation where their own economic well being is at stake.